Tecnica e libertà - Lissa, Giuseppe (Fuori collana, 2022)
Is it the man who dispose of the technique or is the technique that the man has at his disposal? This is probably the fundamental question around which the reflection of this volume rolls around. A reflection that, in consideration of the relationship between contemporary man and technology, also proceeds in the direction of an elaborative proposal that promises the possibility of converting the freedom of the individual into responsibility. Only this step will allow, in fact, to transform the individual's expansion into ethical expansion and to give life to a new humanism, the humanism of the other man, capable of transforming the individual from fomenter of war into one of peace; from dissipator into authentic builder of the future.